2019
DOI: 10.3390/nu11071624
|View full text |Cite
|
Sign up to set email alerts
|

Health Benefits of Resveratrol in Kidney Disease: Evidence from In Vitro and In Vivo Studies

Abstract: Different diseases and disorders that affect the kidneys include, but are not limited to, glomerulonephritis, diabetic nephropathy, polycystic kidney disease, kidney stones, renal fibrosis, sepsis, and renal cell carcinoma. Kidney disease tends to develop over many years, making it difficult to identify until much later when kidney function is severely impaired and undergoing kidney failure. Although conservative care, symptom management, medication, dialysis, transplantation, and aggressive renal cancer thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 117 publications
(261 reference statements)
2
53
0
1
Order By: Relevance
“…Notably, in our intervention study resveratrol treatment did not only alleviate pro-inflammatory immune responses in the intestinal tract, but also in extra-intestinal and even systemic compartments of C. jejuni infected mice given attenuated pro-inflammatory cytokine secretion in the kidneys, the liver and the systemic blood stream. Our results are supported by multiple studies reporting potent anti-inflammatory effects of resveratrol in the kidneys, as shown in rat mesangial cell and human renal epithelial cells in vitro, for instance, and in several renal in vivo inflammation models as recently reviewed by Den Hartogh and colleagues [44]. Furthermore, anti-inflammatory and anti-oxidant effects of resveratrol were described in hepatic ischemic reperfusion injuries in diabetic rats [45] and in experimental as well as in clinical non-alcoholic fatty liver disease [46,47].…”
Section: Discussionsupporting
confidence: 87%
“…Notably, in our intervention study resveratrol treatment did not only alleviate pro-inflammatory immune responses in the intestinal tract, but also in extra-intestinal and even systemic compartments of C. jejuni infected mice given attenuated pro-inflammatory cytokine secretion in the kidneys, the liver and the systemic blood stream. Our results are supported by multiple studies reporting potent anti-inflammatory effects of resveratrol in the kidneys, as shown in rat mesangial cell and human renal epithelial cells in vitro, for instance, and in several renal in vivo inflammation models as recently reviewed by Den Hartogh and colleagues [44]. Furthermore, anti-inflammatory and anti-oxidant effects of resveratrol were described in hepatic ischemic reperfusion injuries in diabetic rats [45] and in experimental as well as in clinical non-alcoholic fatty liver disease [46,47].…”
Section: Discussionsupporting
confidence: 87%
“…The levels of total protein were significantly reduced; however, this occurring independent of other markers (creatinine and uric acid) does not indicate any compelling support for the positive effects of resveratrol supplementation in improving renal function. Although evidence from clinical settings is scarce, preclinical studies have suggested that resveratrol may have a protective effect against renal diseases, through attenuation of oxidative stress and the activation of NAD-dependent deacetylase sirtuin-1 (SIRT1), as reviewed elsewhere [51][52][53]. Thus, additional long-term clinical studies are required to directly assess the combined impact of resveratrol and metformin in managing T2D and its related complications.…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol treatments of the CRL-2573 rat kidney cell line and mesangial primary cells prevented the fibronectin expression and the proliferation of high glucose-induced mesangial cells, respectively (109). Resveratrol decreased atrophy in skeletal muscles in chronic muscle disease via the muscle-specific ringfinger protein 1 (MURF1) signaling pathway (92).…”
Section: Polyphenols Microbiota and Ckdmentioning
confidence: 99%